The Study of the Literacy Pattern and its Differentials in Uttar Dinajpur District, West Bengal - Verma, Narender; Roy, Arpita (National Geographical Journal of India, 2022)
Literacy is a significant qualitative indicator for both social and economic development of a society. It influences fertility, mortality, mobility and economic composition of the population of a region. Literacy pattern of an area is largely influenced by various factors, such as degree of urbanization, nature of economy, standard of living, cost of education, level of technological growth, level of transportation and communication development, religious background, status of females in society, biasness against the female literacy and mobility, political background, availability of educational institutions, public policies etc. This paper attempts to study the spatial pattern of literacy in Uttar Dinajpur district. It is one of the country’s 250 most backward districts and has the lowest literacy in West Bengal. The present study is based on secondary data. Three indices namely Male-Female Differential Index, Rural-Urban Differential Index and Composite Differential Index have calculated to assess the level of development of literacy in the district. From the results it can be observed that Islampur Subdivision in the North lags behind Raiganj subdivision. Blockwise Hemtabad block is most developed whereas Goalpokhar-I block is least developed in literacy in the district.